Ein Beitrag zur viskoelastischen Modellierung nichtholonomer Bindungsgleichungen - Deppler, Jens (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2017)
Based on a formalism to simulate mechanical rigid body systems with plane frictional contacts, an extension to systems with rolling contacts is proposed. A special focus is put on tagential contact compliance. A mathematical convergency proof of the solution of the tangential elastic formulation to the rigid one is proposed.